Universities in Crisis and Recovery: The Case of Hong Kong, China - Postiglione, Gerard (International Higher Education, 2020)
Universities moved to the center of the Hong Kong protest movement, while Hong Kong moved into the front line of the US-China trade war. Like other world cities with top-tier universities, Hong Kong has reason to expect that its universities will make a full recovery.